AUTHORITY OF CLASS I PENITENTIARIES BANDAR LAMPUNG AS A PUBLIC SERVICE IN HANDLING GLOBAL PANDEMIC - Gromiko, Alek; Baharudin, Baharudin; R, Rosita (Jurnal Al-Dustur, 2023)
Prisons are closed places with high occupancy rates and are very vulnerable to the spread of Global Pandemic, so a policy from the government is needed to prevent the spread of Global Pandemic in the prison environment..This study uses a normative juridical approach and an empirical juridical approach. Collecting data by field studies and literature studies. Data analysis was carried out in a qualitative juridical manner, namely the analysis was carried out descriptively. Research results discussImplementing prison authoritiesis a Class I prison policy in Bandar Lampung which applies visitation restrictions for inmates in the form of online visits via Whatsapp media based on the instructions of the Director General of Corrections Number: PAS-08.OT.02.02 of 2020 concerning Prevention, Handling, Control and Recovery of Corona Virus Disease (Global Pandemic) at the Correctional Technical Implementation Unit. The inhibiting factor consists of interference with the internet connection at the destination number. is a network problem that is used for online visitation services with the Correctional Database System and does not yet have a special network with the Correctional Database System and the current factor of facilities for video call services is still very lacking, because when conditions are crowded the queues of inmates to be able to use online visit services are sufficient long.